PENGARUH MODEL CHALLENGE BASED LEARNING TERHADAP KEMAMPUAN KONEKSI MATEMATIS SISWA - Arifin, Reina Stevany; Solihah, Sri; Ruswana, Angra Meta (Faculty of Teacher Training and Education, 2026)
The background of this study is ineffective mathematics learning, which has an impact on students' low mathematical connection abilities. This study aims to determine the effect of the challenge based learning model on students' mathematical connection abilities. The research method used is a quasi experiment with a Non-equivalent Pretest-Posttest Control Group Design. The population in this study were all students of grade VII at MTs Negeri 2 Ciamis, with a sample of two classes, namely class VII F as the experimental class and class VII E as the control class selected through purposive sampling techniques. Data analysis techniques were carried out through pretests and posttests of mathematical connection abilities which were analyzed using normality tests, homogeneity tests, two-mean difference tests, and effect sizes. The results showed that there were differences in mathematical connection abilities between the experimental class using the challenge based learning model and the control class using the conventional learning model. Thus, it can be concluded that the challenge based learning model has an effect on students' mathematical connection abilities. Latar belakang penelitian ini adalah pembelajaran matematika yang belum efektif, sehingga berdampak pada rendahnya kemampuan koneksi matematis siswa. Penelitian ini bertujuan untuk mengetahui pengaruh model challenge based learning terhadap kemampuan koneksi matematis siswa. Metode penelitian yang digunakan adalah quasi experiment dengan desain Non-equivalent Pretest-Posttest Control Group Design. Populasi dalam penelitian ini adalah seluruh siswa kelas VII di MTs Negeri 2 Ciamis, dengan sampel dua kelas, yaitu kelas VII F sebagai kelas eksperimen dan kelas VII E sebagai kelas kontrol yang dipilih melalui teknik purposive sampling. Teknik analisis data dilakukan melalui pretest dan posttest kemampuan koneksi matematis yang dianalisis menggunakan uji normalitas, uji homogenitas, uji perbedaan dua rata-rata, dan effect size. Hasil penelitian menunjukkan bahwa terdapat perbedaan kemampuan koneksi matematis antara kelas eksperimen yang menggunakan model challenge based learning dan kelas kontrol yang menggunakan model pembelajaran konvensional. Dengan demikian, dapat disimpulkan bahwa model challenge based learning berpengaruh terhadap kemampuan koneksi matematis siswa.